Expression of ACE2, the SARS-CoV-2 Receptor, in Lung Tissue of Patients With Type 2 Diabetes - Wijnant, Sara R.A.; Jacobs, Merel; Van Eeckhoutte, Hannelore P.; Lapauw, Bruno; Joos, Guy F.; Bracke, Ken R.; Brusselle, Guy G. (Diabetes (New York, N.Y.), 2020)
Increased expression of pulmonary ACE2, the SARS-CoV-2 receptor, could contribute to increased infectivity of COVID-19 in patients with diabetes, but ACE2 expression has not been studied in lung tissue of subjects with diabetes. We therefore studied ACE2 mRNA and protein expression in lung tissue samples of subjects with and without diabetes that were collected between 2002 and 2020 from patients undergoing lobectomy for lung tumors. For RT-PCR analyses, samples from 15 subjects with diabetes were compared with 91 randomly chosen control samples. For immunohistochemical staining, samples from 26 subjects with diabetes were compared with 66 randomly chosen control samples. mRNA expression of ACE2 was measured by quantitative RT-PCR. Protein levels of ACE2 were visualized by immunohistochemistry on paraffin-embedded lung tissue samples and quantified in alveolar and bronchial epithelium. Pulmonary ACE2 mRNA expression was not different between subjects with or without diabetes. In contrast, protein levels of ACE2 were significantly increased in both alveolar tissue and bronchial epithelium of patients with diabetes compared with control subjects, independent of smoking, chronic obstructive pulmonary disease, BMI, renin-angiotensin-aldosterone system inhibitor use, and other potential confounders. To conclude, we show increased bronchial and alveolar ACE2 protein expression in patients with diabetes. Further research is needed to elucidate whether upregulation of ACE2 expression in airways and lungs has consequences on infectivity and clinical outcomes of COVID-19.